PENGARUH IMPLEMENTASI KEBIJAKAN AUDIT PENERIMAAN NEGARA BUKAN PAJAK (PNBP) TERHADAP KINERJA AUDITOR PADA PUSAT PENGEMBANGAN DAN PENATARAN GURU IPA KOTA BANDUNG - Nanang Suparman (Jurnal Akuntansi dan Perpajakan, 2017)
TheNon-Tax Revenue policy as an implementative rules from laws, is an policy in attempt for collection and managing mechanism of non-tax revenue. Consequently, such policy has determined various preventive and repressive rules on deviation behavior toward state financial righats. The effective of audit policy of all activities link that must be applied by such performance.Both from organizational, interpretative, and application aspects.Owned professional ethics of auditors to the adherence to the policy in order to improve the performance of supervisory auditor.Therefore, it is carried out an evaluation on auditor supervisory performance throughout state financial rights security indicators, adherence on auditing administrative policy and process. Research variables consist of activities in implementation of non-tax state revenue audit policy, namely: organizing,interpreting,and application as independent variables, meanwhile its auditor supervisory performance is observed from organizational intern controlling system, namely:protection of state financial rights, adherence on auditing administrative policy and process as dependent variables. DOI: https://doi.org/10.26905/ap.v3i1.1326